Anti-Tuberculosis Drug - Induced Hepatitis – A Case Report - K, Amer; A, Mir ShoebUlla; SA, Aamir; K, Nematullah; S, Ihtisham; M, Maazuddin (Indian Journal of Pharmacy Practice)
Introduction: This is a case report focusing on a 32 years male patient who experienced hepatotoxicity after administration of anti tubercular drugs. Isoniazid, Rifampacin, Pyrazinamide, Ethambutol are the first line agents in the treatment of Tuberculosis. The incidence rate of anti-TB induced hepatotoxicity is found to be 2% to 28%. Case: In this case, the patient was receiving anti-tubercular drugs from 3 months and developed hepatitis which is a severe adverse drug reaction. Naranjo's causality assessment algorithm was used to assess the adverse effect and it indicated anti-tubercular drugs as probable cause of hepatitis.
Keywords: Hepatitis; Anti-tubercular drugs; SGOT(serum glutamic oxaloacetic transaminase); SGPT(serum glutamic pyruvic transaminase)